2022
DOI: 10.20344/amp.11987
|View full text |Cite
|
Sign up to set email alerts
|

Uterine Compression Sutures in Controlling Postpartum Haemorrhage: A Narrative Review

Abstract: Introduction: Postpartum haemorrhage is still the main cause of maternal morbidity and mortality. Many treatments are available, but they may threaten fertility potential. As a uterine sparing procedure, we aimed to review uterine compression sutures in order to better understand when they should represent an appropriate option.Material and Methods: A comprehensive search in MEDLINE and PubMed databases including the terms ‘postpartum haemorrhage’ and ‘uterine compression sutures’ was performed. Results were r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 52 publications
1
14
0
2
Order By: Relevance
“…Different from Matsubara's and Aboulfalah's removable UCS per the abdominal wall, our RRUCS is not only convenient for postoperative removal of the threads, but also has less puncture points on the uterus and the abdominal wall, thereby minimizing the adverse events of UCS. Its success rate in instant bleeding stoppage was 92.31% (36/39), which matched those of other authors' reports 1, 3, 5, 6, 19–22 . Moreover, no adverse events were detected in women who underwent RRUCS.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Different from Matsubara's and Aboulfalah's removable UCS per the abdominal wall, our RRUCS is not only convenient for postoperative removal of the threads, but also has less puncture points on the uterus and the abdominal wall, thereby minimizing the adverse events of UCS. Its success rate in instant bleeding stoppage was 92.31% (36/39), which matched those of other authors' reports 1, 3, 5, 6, 19–22 . Moreover, no adverse events were detected in women who underwent RRUCS.…”
Section: Discussionsupporting
confidence: 86%
“…Complications after UCS have attracted obstetricians' attention for decades, and various approaches to solve the problem have been constantly searched. Some adverse events, such as uterine ischemia, erosion, necrosis, rupture, synechia, infection, reinversion, irregular menstruation, and menstruation‐associated symptoms or depression, have been repeatedly described following UCS 7–10, 17–24 . Seidel et al 25 reported a patient with vaginal omentum prolapse after prophylactic UCS, in whom a hysterectomy was performed owing to serious uterine necrosis, infection, and destruction.…”
Section: Discussionmentioning
confidence: 99%
“…In a review published in 2019 regarding uterine compression sutures, the success rate of different compression suture techniques in postpartum bleeding was reported between 36% and 98%. In the same review, since there hadn't been any randomized controlled studies comparing suture techniques in the literature, it was suggested that suture technique selection should be made according to the surgeon's knowledge and experience regarding the case (23).…”
Section: Discussionmentioning
confidence: 99%
“…La literatura existente ha encontrado que la atonía uterina como representante más común de la hemorragia posparto está asociada a un alto índice de muertes maternas a nivel mundial (14). Este estudio refleja la efectividad de la técnica de B-Lynch como tratamiento en la hemorragia por atonía uterina, permitiendo la preservación del útero y la fertilidad.…”
Section: Discussionunclassified